Conversas sobre matemática com pessoas idosas viabilizadas por uma ação de extensão universitária - Lima, Luciano Feliciano de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This text refers to research focused is a University Extension action as a way to enable a dialogue on Mathematics with elderly people, having as guideline question 'What is shown in an action of University Extension involving conversations about mathematics with older people?'. Actions involving education for elderly people are present in Brazilian society, through the University Extension. However, there is a lack of research relating the education of elderly and mathematics. To contribute to discussions in this direction, through this work we try to reflect on the research question: What is shown in an action of University Extension involving conversations about mathematics with older people? Therefore, the action called Conversations on Mathematics was developed with a group of people over the age of 50, held in fortnightly meetings over a year, each lasting one hour. At the meetings were suggested mathematical subjects as loans for retirees, Moebius strip, numerical regularities, symmetries among others, using various resources. The mathematical subjects of the meetings were developed from an investigative approach in a critical education perspective. The survey data, a qualitative one, were made based on the researcher's field diary, the transcripts of interviews of eight participants of Conversations action and the group's productions. Data analysis showed two themes that contribute to the reflection of the guideline question, namely: Reasons to attend the action Conversations and Participation. The participation of the elderly ladies and gentlemen on the Conversations action were perceived through their engagement in order to develop mathematical tasks through an investigative approach, through their interest in understanding the problems and their work to solve them. It was also noticed when participants expressed themselves on the subject discussed, making inquiries, positioning itself with your ideas and defending them with...

Este texto apresenta uma pesquisa cujo foco é uma ação extensionista que visou possibilitar um diálogo sobre Matemática com pessoas idosas, tendo como pergunta diretriz 'O que se mostra em uma ação de Extensão Universitária envolvendo conversas sobre Matemática com pessoas idosas?'. Ações envolvendo educação de idosos estão presentes no cenário brasileiro por meio da Extensão Universitária, no entanto, há uma carência de pesquisas relacionando a educação de idosos e a Matemática. Visando contribuir com discussões nesse sentido, foi desenvolvida a ação denominada Conversas sobre Matemática com um grupo de pessoas com idade superior a 50 anos, que se realizou em encontros quinzenais ao longo de um ano, cada um com duração de uma hora. Nos encontros eram sugeridos assuntos matemáticos como empréstimos para aposentados, faixa de Moebius, regularidades numéricas, simetrias entre outros, utilizando recursos variados. Os assuntos matemáticos dos encontros foram desenvolvidos a partir de uma abordagem investigativa numa perspectiva de educação crítica. Os dados da pesquisa, de cunho qualitativo, foram constituídos por meio do diário de campo do pesquisador, pelas transcrições das entrevistas de oito participantes da ação Conversas e pelas produções do grupo. A análise dos dados mostrou duas temáticas que contribuem para a reflexão da pergunta diretriz, quais sejam: Motivos para frequentar a ação Conversas e Participação. Em relação aos Motivos para frequentar a ação Conversas apresentam-se: contribuições das tarefas matemáticas para a cognição; possibilidades de interações sociais e de aprender coisas novas; desejo de aprender; gosto pela Matemática. Em relação a Participação mostram-se: realização das tarefas sugeridas; perguntas, respostas e considerações sobre os assuntos matemáticos discutidos; experimentação com os materiais disponibilizados; compartilhamentos do que foi...
Keywords: Teachers, Training of; Matemática - Estudo e ensino; Idosos - Educação; Dialogo; Extensão universitaria; Parkinson, Doença de; Motivação na educação